Computerised Cell Voltage Monitoring at the Electrolytic Refining and Smelting Company of Australia Limited Port Kembla NSW Australia - A. Christlo (The Minerals, Metals and Materials Society, 1987)
Short circuit detection in 1984 involved nine inspectors for production rates of 43,000 tpa. Trials indicated the feasibility of applying cell voltage monitoring to short circuit detection and improving operational efficiency. A computerised cell voltage monitoring system was commissioned in February 1986, to read voltages from 648 cells. The system incorporates 16 evenly distributed work face units which communicate with a central computer system. Provision has been made in the computer program for the automatic adjustment of cell reference voltages. This allows for the effect of polarization and other process variables which might other wise interfere with short circuit detection. The work face units can continue to work independently for several days should this become necssary. Current efficiencies have been maintained and the number of inspectors reduced from nine to five.